Low TGF-β1 in Wound Exudate Predicts Surgical Site Infection After Axillary Lymph Node Dissection - Leppäpuska Ida M; Rannikko Eeva H; Laukka Mervi; Peuhu Emilia; Veemaa Raili; Viitanen Tiina; Koskivuo Ilkka; Hartiala Pauliina (United States, 2022)
Purpose
Surgical site infection (SSI) after axillary lymph node dissection (ALND) for breast cancer increases morbidity and delays the onset of adjuvant treatment. Only a few studies have investigated the feasibility of wound exudate analysis in SSI prediction. This study assessed changes in cytokine levels in postsurgical wound exudate after ALND and examined their predictive value for the early diagnosis of SSI.
Methods
An observational prospective pilot study was conducted in 47 patients with breast cancer undergoing ALND. Wound exudate samples were collected on the first and sixth postoperative days (POD). Interleukin (IL)-1α, IL-1β, IL-4, IL-10, IL-13, tumor necrosis factor alpha (TNF-α), transforming growth factor beta1 (TGF-β1) and vascular endothelial growth factor (VEGF) C and D levels were measured by immunoassay. Patients were followed to detect SSI.
Results
SSI was diagnosed in 8/47 (17.0%) patients. Four SSI patients were hospitalized and treated with intravenous antibiotics. The concentration of TGF-β1 in wound exudate was significantly lower on POD#1 in the SSI group compared to the no SSI group (p=0.008). The receiving operator characteristics (ROC) curve for TGF-β1 showed an area under curve of 0.773 (p=0.0149) indicating good diagnostic potential. On POD#6, the concentration of TGF-β1 remained significantly lower (p=0.043) and the concentrations of IL-10 (p=0.000) and IL-1β (0.004) significantly higher in the SSI group compared to the no SSI group.
Conclusion
To our knowledge, this is the first study suggesting a predictive role of wound exudate TGF-β1 levels for SSI. Our results suggest that the risk for SSI can be detected already on POD#1 and that the assessment of TGF-β1 levels in the wound exudate after ALND can provide a usefull method for the early detection of SSI. The key findings of this pilot study warrant verification in a larger patient population.